EFFECTIVENESS OF WETLAND-BASED WAVE AND OPTICS MODULES ON STUDENTS' SCIENTIFIC LITERACY ABILITIES - Khairunnisa, Yasmine; Hafizah, Ellyna; Salupi, Wida (Universitas Tanjungpura, 2024)
Wetlands that dominate the area in South Kalimantan are one of the indigenous science learning resources that can help students learn. However, the insertion of wetlands has not commonly been done on a learning media which directly used in class. The developed wetlands-based module on wave and optics aimed to enhance students